Chemical Composition and Sensory Quality of Coffee Fruits at Different Stages of Maturity - Valentina Osorio Pérez; Luis Gerónimo Matallana Pérez; Mario Roberto Fernandez-Alduenda; Cristina Inés Alvarez Barreto; Claudia Patricia Gallego Agudelo; Esther Cecilia Montoya Restrepo (Agronomy, 2023)
The configuration of the sensory quality of coffee begins in the tree, where chemical precursors are deposited and formed in the seeds as the fruits develop. Fruit within the range classified as mature can have a wide range of properties. This study evaluated three degrees of maturity and established their chemical and sensory characteristics using analytical techniques such as liquid and gas chromatography. The maturity states evaluated did not show differences in organic acids, free fatty acids, lipids, total chlorogenic acids, proteins, alkaloids or sucrose. Fructose and glucose showed differences with respect to the degree of maturity, with higher values associated with more developed states. The analysis of variance did not show a significant effect on sensory attributes or sensory quality. The chromatic coordinate a* of the CIEL*a*b* scale reached a maximum value of 25.16, and the evaluated states were different from each other.